Cultural generations or a reproduced generation in Algeria? An epistemo-sociological reading of the thought of Nacer Djabi - Sallay, Kamel; Bouzidi, Lahouari (The International tax journal, 2025)
Through his approach to “possible conflictuality” between generational moments in Algeria, the sociologist Nacer Djabi raises a set of epistemic issues that have unfolded amid new waves of social movements that have characterised the world since the dawn of the third millennium. At the forefront of these issues lies a fundamental question: What challenges do the third generation continue to face in mobilising contemporary society? However, the hermeneutic coercion that has persistently stifled the mechanisms of reflection on these matters has remained confined to the realm of logical absolutes, which have uncritically endorsed the coordinates of an "Algerian-style transition". This has prompted us to investigate the genealogy of the knowledge system that has shaped this episteme in an identitarian manner. Accordingly, this article aims to develop a critical reading that reassesses, first, the conceptualisation of the “cultural generation” and, second, the narrative of “generational conflict”. This will be achieved by engaging with two principal questions raised by the researcher: Does Algeria's demographic stratification reflect cultural diversity indicative of historical blocs? Moreover, do the youth-centred tendencies of new university graduates constitute a cultural generation?